Direct Costs of Parkinson’s Disease at Suratthani Central Hospital: a Retrospective Study - Techakehakij, Win; Kanyamee, Pattaraporn (Journal of Health Science of Thailand, 2017)
Parkinson’s disease (PD) is a progressive neurologic disease in which patients commonly present with abnormal movements. The prevalence of PD in Thailand was 242.57 per 100,000 in 2011, with more than 60,000 PD patients being reported. Progressive disability associated with PD not only affects physical health, but also causes economic burdens for the healthcare system. However, little is known about the costs of PD in Thailand. This study aims to estimate the direct costs of PD. Cost data were retrieved from the medical records of PD patients who were treated at the Parkinson’s clinic at Suratthani Central Hospital in 2014. The total direct costs (TDCs) of PD, including direct medical costs (DMCs) –unit costs for out-patient and in-patient services, PD-related medications and other medical services, and laboratory investigations; and direct non-medical costs of the patients, were approximated, with 2014 as the base year. Means of the annual TDCs and annual DMCs were compared across sex and age groups, using t-tests and ANOVA. There were 153 PD patients identified, with 49.7% being males. Fifteen percent of patients aged less than 60, 67.3% aged 60-79, and 17.7% aged 80 and above. The annual DMCs and annual TDCs of PD were baht 26,314.3 and 29,476.0, respectively. Statistics showed moderate evidence indicating higher costs of both annual TDCs and annual DMCs in males compared to females. With 60,000 annual cases of PD in Thailand, the estimated DMCs of PD could exceed 1.57 billion baht per annum. This sizable economic impact of PD emphasizes the importance of considering efficiency when making policy decision about novel PD-related interventions.